Community health worker-delivered counselling for common mental disorders among chronic disease patients in South Africa: A feasibility study - Myers-Franchi, Bronwyn; Petersen-Williams, P.; Van Der Westhuizen, C.; Lund, C.; Lombard, C.; Joska, J.A.; Levitt, N.S.; Butler, C.; Naledi, T.; Milligan, P.; Stein, D.J.; Sorsdahl, K. (BMJ PUBLISHING GROUP, 2019)
Objectives: To examine the feasibility and acceptability of integrating a 'designated' approach to community health worker (CHW)-delivered mental health counselling (where existing CHWs deliver counselling in addition to usual duties) and a 'dedicated' approach (where additional CHWs have the sole responsibility of delivering mental health counselling) into chronic disease care.